2020
DOI: 10.1186/s12886-020-01355-7
|View full text |Cite
|
Sign up to set email alerts
|

Biometric indicators of eyes with occult lens subluxation inducing secondary acute angle closure

Abstract: Background: To compare the anterior biometrics in eyes with secondary acute angle closure induced by occult lens subluxation (ASAC-LS), misdiagnosed as acute primary angle closure (APAC) at the first visit with APAC, chronic primary angle closure glaucoma (CPACG), and cataract. Methods: This retrospective case study included 17 eyes with angel closure due to occult LS, who were misdiagnosed as APAC on their first visit, 56 APAC eyes, 54 CPACG eyes, and 56 cataract eyes. Axial length (AL), central corneal thick… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
0
9
1
Order By: Relevance
“…Based on our analysis, ACD < 1.4 mm and ACD difference > 0.63 mm are highly indicative of abnormal lens zonular dehiscence or relaxation. Unlike our study, Xing suggested that ACD < 1.25 mm reflected lens subluxation in their study (12). The difference in our studies may be due to the analysis of small sample sizes.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Based on our analysis, ACD < 1.4 mm and ACD difference > 0.63 mm are highly indicative of abnormal lens zonular dehiscence or relaxation. Unlike our study, Xing suggested that ACD < 1.25 mm reflected lens subluxation in their study (12). The difference in our studies may be due to the analysis of small sample sizes.…”
Section: Discussioncontrasting
confidence: 86%
“…Lens subluxation is a multifactorial condition that involves a common malpositioning of the lens, likely due to the partial zonular dehiscence or zonular laxity/weakness (12). Among the 20 lens subluxation cases examined in this study, 7 were caused by trauma, 2 cases by high myopia, 1 case by RP, 1 case had familial lens subluxation, 1 case had spontaneous lens subluxation, and the remaining cases had unknown causes.…”
Section: Discussionmentioning
confidence: 89%
“… 16 , 19 Multiple studies have described angle closure in the setting of disrupted lens zonule anatomy, leading to abnormal lens configuration or position. 20 , 21 , 22 , 23 Given the examination and imaging findings in this patient, the ciliary body cysts, in combination with the lens abnormalities, were the essential contributor to the angle closure.…”
Section: Discussionmentioning
confidence: 87%
“…The high proportion of zonulopathy in PACD has been observed and has been emphasized by glaucoma specialists during surgical care. Previous studies regarding zonulopathy in patients with ACG have included some cases with zonulopathy, secondary to trauma or other etiologies including pseudoexfoliation syndrome, retinitis pigmentosa, etc 13,21–23 . In this study, we investigated intraoperatively diagnosed zonulopathy in patients with PACD having no history of trauma or other known causes of zonulopathy.…”
Section: Discussionmentioning
confidence: 99%
“…According to the receiver operating characteristic curve analysis, the ACD in the study eyes and the intereye asymmetry ACD contributed to the differential diagnosis of acute PAC and secondary AAC with cutoff values of 1.4 and 0.63 mm, respectively. Xing et al 22 found that the subjects with AAC secondary to lens subluxation had longer AL, smaller ACD, and thicker LT compared with the acute and chronic PACG subjects. According to the receiver operating characteristic curve study, RLP and ACD illustrated a high discrimination for the group with ACG secondary to zonulopathy.…”
Section: Discussionmentioning
confidence: 99%